Understanding Anthracycline Cardiotoxicity From Mitochondrial Aspect - Huang, Junqi; Wu, Rundong; Chen, Linyi; Yang, Ziqiang; Yan, Daoguang; Li, Mingchuan (Frontiers in Pharmacology, 2022)
Anthracyclines, such as doxorubicin, represent one group of chemotherapy drugs with the most cardiotoxicity. Despite that anthracyclines are capable of treating assorted solid tumors and hematological malignancies, the side effect of inducing cardiac dysfunction has hampered their clinical use. Currently, the mechanism underlying anthracycline cardiotoxicity remains obscure. Increasing evidence points to mitochondria, the energy factory of cardiomyocytes, as a major target of anthracyclines. In this review, we will summarize recent findings about mitochondrial mechanism during anthracycline cardiotoxicity. In particular, we will focus on the following aspects: 1) The traditional view about anthracycline-induced reactive oxygen species (ROS), which is produced by mitochondria, but in turn causes mitochondrial injury. 2) Mitochondrial iron-overload and ferroptosis during anthracycline cardiotoxicity. 3) Autophagy, mitophagy and mitochondrial dynamics during anthracycline cardiotoxicity. 4) Anthracycline-induced disruption of cardiac metabolism.